2017
DOI: 10.3892/or.2017.5830
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Bcl-2 plays an important role in glycochenodeoxycholate-induced survival and chemoresistance in HCC

Abstract: Abstract. Hepatocellular carcinoma (HCC) is a highly malignant tumor and can evolve rapidly to resistance to chemotherapies. Glycochenodeoxycholate (GCDA), which is toxic and hydrophobic, is the main ingredient in the bile and associated with carcinogenesis of gastrointenstinal tumors. Bcl-2 is the most important anti-apoptotic protein and overexpressed in various human tumors. In the present study, we found that GCDA can induce the chemoresistance of human liver cancer cells and specific depletion of Bcl-2 by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…8). Regarding the undetectable Bcl-2 expression in the Huh-7 cells, Wang et al (34) reported a similar result; however certain studies have detected it, but reported that it was lower in Huh-7 cells compared with other hepatoma cell lines (35,36). There is a possibility that the expression of Bcl-2 was not detected in the present study due to different experimental conditions.…”
Section: Discussionsupporting
confidence: 59%
“…8). Regarding the undetectable Bcl-2 expression in the Huh-7 cells, Wang et al (34) reported a similar result; however certain studies have detected it, but reported that it was lower in Huh-7 cells compared with other hepatoma cell lines (35,36). There is a possibility that the expression of Bcl-2 was not detected in the present study due to different experimental conditions.…”
Section: Discussionsupporting
confidence: 59%
“…However, the way of ICT1 regulating BCL-2 is unknown. The previous studies reported that BCL-2 is an anti-apototic molecule, which is phosphorylated at Ser70 by growth factor-activated protein kinases including PKC and the MAPKs (ERK1/2) can actively control the anti-apoptotic function of BCL-2 [28][29][30]. It is unclear that wheather ICT1 leads to phosphoylation of BCL-2 to inhibit apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…After treatment, the cells were harvested and the whole-cell extracts were prepared as the method previously described [26]. Protein concentration was measured according to the BAC Assay Reagent.…”
Section: Cell Extraction and Western Blottingmentioning
confidence: 99%
“…Protein concentration was measured according to the BAC Assay Reagent. Western blot was performed as the protocol described before [26].…”
Section: Cell Extraction and Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation